Glad - Odor, Ruth Shannon; Inderieden, Nancy (Elgin, Ill. : Child's World ; Chicago : distributed by Childrens Press, 1980)
A child talks about all the things that make her glad and what a good feeling it is.
Keywords: Happiness; Happiness